The Negros Millenarian movements - Cleope, Earl Jude Paul L. (2001)
This paper presents the millenarian movements of Negros Island, specifically in the southern part where topographic conditions significantly influenced the emergence and subsequent reappearance of what is sometimes labeled as "revitalization movements." Further, this paper aims to present the various peasant movements with their religious undertones which appeared in Negros as babaylanism from nearby Panay Island. Hence, this paper tries to elucidate the connection between the movement spearheaded by Dios Buhawi in 1888; Papa Isio in the 1890s; the Salvatorri(e) in the 1980s; and the contemporary "Dios Amahan" movements. Interestingly, all of these movements found fertile breeding ground in the same areas.